Alternate history - Niefanger, Dirk (Critical Terms in Futures Studies, 2019)
This chapter understands alternate history less as a genre or subgenre of literature, and more as a unique type of diegesis primarily defined by its content, found in various media and genres. Understood in this way, alternate histories seem at first glance to deal with the past, yet they always do so with the obvious purpose of changing our present and our future. Every alternate history looks at what are considered the flaws of the present, as much as examining the possibilities for improving it by rehearsing several scenarios.
CRIS-Team Scopus Importer:2021-04-20